PERAN POLRES PULAU AMBON & PP. LEASE TERHADAP TAWURAN ANTAR PELAJAR DI KOTA AMBON DITINJAU DARI HUKUM ISLAM - Fauzia Rahawarin (TAHKIM, 2017)
Brawl between students often occurs in the Ambon city. This study aims to determine how the handling of police Polres Pulau Ambon & PP. Lease of the brawl between students in the city of Ambon, and to find out how Islamic legal review of the brawl between students in the Ambon city. This type of research is the field Research. The type of data used are primary data and secondary data sourced from the study site and literature. Data were analyzed by deductive and inductive. Police handling of the brawl, the process of handling and guidance of the police that data held school of origin, residence address, ordered to perform physical activities and asked the whereabouts of parents. After that call, the parents and from the school, was given guidance by the police Polres Pulau Ambon & PP. Lease. According to Islamic law, students who are involved fighting between students can not be sentenced to a criminal, because immature. In addition, the handling of fighting between students in the Ambon city, according to Islamic law is coaching actors brawl between students, both the parents and teachers at school. Keywords: brawl, students, criminal liability, Islamic law